La lecture académique dans la perspective d’un écrit de transition - Wojciechowska, Bernadeta; Karpińska-Szaj, Katarzyna (Studia Romanica Posnaniensia, 2025)
Academic reading can have different epistemic objectives and be situated at different levels, such as the development of disciplinary knowledge, the observation and development of scientific reasoning, as well as the awareness and refinement of reading strategies. From the pedagogical perspective, given the cognitive complexity of academic reading, it is advisable to combine academic reading tasks with writing tasks, the so-called intermediate genres (reading report, reformulation, summary). The aim of this article is to examine how MA students in Romance languages evaluate their reading strategies both in paired discussions after reading an article and in written reformulation, with a view to using its content in approaching a new research problem.